2005
DOI: 10.2478/bf02475199
|View full text |Cite
|
Sign up to set email alerts
|

The influence of temperature and photoinitiator concentration on photoinitiated polymerization of diacrylate monomer

Abstract: The behavior of p-methoxybenzoyldiphenylphosphine oxide, previously synthesized, as a photoinitiator for the polymerization of diacrylate monomer, in the presence of 3 % (w/w) tertiary amine (triethyl amine) as synergist additive, was studied. The influence of temperature in the range 30-90 • C at 3 % (w/w) photoinitiator concentration and the influence of the photoinitiator concentration in the range 0.5-3.5 % (w/w) at 30 • C was investigated by differential scanning photocalorimetry (photo-DSC). In all exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…In the series without solvent, VD-TPOL (3 mol%) showed higher Gʹ around 18.1 MPa in within 6s than VD-TPOL (1 mol%) and VD-TPOL(5 mol%), while Gʹ of VD-TPOL (3 mol%) reached up to 11.3 MPa within 12 s in the presence of a solvent, which means the solvent decreased the cross-linking rate due to the chain transfer agent [ 118 ]. In the case of VDM resin, the Gʹ value for VDM-TPOL (5 mol%) was higher in the presence of solvent than VDM-TPOL (1 mol%) and VDM-TPOL (3 mol%), which was due to more cross-linking on the surface layer and the slow polymerization [ 119 , 120 ].…”
Section: Vn-based Resinsmentioning
confidence: 99%
“…In the series without solvent, VD-TPOL (3 mol%) showed higher Gʹ around 18.1 MPa in within 6s than VD-TPOL (1 mol%) and VD-TPOL(5 mol%), while Gʹ of VD-TPOL (3 mol%) reached up to 11.3 MPa within 12 s in the presence of a solvent, which means the solvent decreased the cross-linking rate due to the chain transfer agent [ 118 ]. In the case of VDM resin, the Gʹ value for VDM-TPOL (5 mol%) was higher in the presence of solvent than VDM-TPOL (1 mol%) and VDM-TPOL (3 mol%), which was due to more cross-linking on the surface layer and the slow polymerization [ 119 , 120 ].…”
Section: Vn-based Resinsmentioning
confidence: 99%
“…To conclude, the hypothesis as stated above with respect to the optimum PhIn content could neither be rejected nor accepted as an optimum could still be apparent for lower PhIn concentrations although 3 wt% is generally used in literature [24,58,63].…”
Section: Impact Of Photo-initiator Contentmentioning
confidence: 93%
“…Therefore, the investigated radiation time range was shortened to 105 s. It was suggested that the efficiency of absorption of the incident radiation by the PhIn increases with the PhIn concentration, resulting in more radicals. A possible explanation, according to [24,45,[58][59][60], is that increasing the PhIn concentration results in a large amount of free radicals, which quickly generate a polymer network.…”
Section: Impact Of Photo-initiator Contentmentioning
confidence: 99%
“…All formulations displayed a similar photopolymerization rate, when the concentration of photoinitiators was varied in the T-E (1:3) HIPEs (Figure 4b), though the HIPEs with 2.0 mol% of both photoinitiators displayed lower reactivity, while the formulation with 0.25 mol% of both photoinitiators showed the highest. Due to the high reactivity of the T-E formulations, conversions of 99%, 98%, 98% and 94% were attained for the formulations with increasing concentration of photoinitiators, after 1200 s. This can be attributed to the rapid build-up of the crosslinked network in the highly viscous media of the HIPE, due to the high concentration of free radicals, hindering the propagation reactions, which results in a decrease in the photopolymerization rate [54,55]. A disadvantage of using high concentration of photoinitiators is the increase in the levels of yellowing.…”
Section: Kinetics Of Photopolymerization Of the Hipesmentioning
confidence: 99%